A Comprehensive Approach to Securing Power Converters: Cyber-Physical Integration - Jha, Rahul Kumar; Neupane, Sumina; Bhatt, Roshan Raj (Recent Research Reviews Journal, 2023)
This paper presents a novel approach for integrating cyber-physical security measures into power converters. As the demand for renewable energy sources continues to grow, the importance of securing the power grid against cyber-attacks becomes increasingly critical. Power converters are a key component of the grid, and their vulnerability to cyber-attacks presents a significant risk to the security and reliability of the system. In this study, a solution that combines traditional physical security measures with advanced cyber-security techniques to provide a comprehensive approach to protecting power converters is proposed. Our approach includes the use of secure communication protocols, intrusion detection systems, and advanced encryption algorithms to safeguard against cyber-attacks. The use of physical security measures, such as tamper-evident seals and monitoring systems, to protect against physical attacks is also explored. The results demonstrate the effectiveness of the approach in mitigating both cyber and physical security threats to power converters, and highlight the importance of integrating cyber-physical security measures into critical infrastructure systems.
Keywords: Access control; Cyber-Physical Systems (CPS); Framework; Firmware Security; Integration; Power Grid; Resilience